Family and Children: Realities and Evaluations - Mitrikas, Alfonsas Algimantas (Sociologija. Mintis ir veiksmas, 2006)
In the paper family life and children having realities and relationships of their evaluations on the basis of corresponding statistical data (about the real situation and its changes), European Values Study and World Values Survey data (about attitudes and evaluations) carried out in 1999-2001 are analysed. Family formation, having children and family life factual status are connected with the world of values, regulations which are reflected in people’s attitudes (and evaluations) about different aspects of life, and about having offspring as well. However, relations of the real state, views and evaluations are not so simple and easily interpreted. Comparing real facts and evaluations we rather often encounter their contradictions. The refore the goal of the paper is to discuss the conditioning circumstances of the contradictions.The main attention is given to the problem of having children. The problem is analysed starting with family formation and impacts on its stability and ending with the phenomena of extra-marital children. The main particularly used indicator of having children is the number of births given by a woman during her life, i.e. total fertility rate (TFR). The questions why the TFR have remained higher and in recent thirty years and there hasn’t been a marked decrease in the European countries where modern viewpoint of family life is backed up are discussed. Relations between the share of extramarital children in different countries and corresponding view of family formation and children having and others are fixed.
Keywords: family; children; total fertility rate; modernist understanding of family life